Responsibility of The Parties in Electronic Transactions - Muhammad Yunus Idy; Abdul Rauf (Jurnal Hukum Volkgeist, 2022)
Electronic transactions are legal relationships between two or more parties that give rise to rights and obligations or responsibilities. The purpose of this study is to find out how the responsibilities of the parties in electronic transactions are, using normative juridical research methods, namely discussing theories and laws and regulations related to the responsibilities of the parties in electronic transactions. The results of the study show that the responsibility of the parties in electronic transactions is not only when an error occurs that causes harm to the other party, but that responsibility exists even before the agreement is signed. Before the agreement is agreed, each party is responsible for providing correct information to the other party, especially related to the products offered. The responsibility after the agreement is to fulfill all agreed clauses. Disputes arising from an electronic transaction can be resolved in two ways, namely litigation through the courts, and settlement through alternative dispute resolution.